Interactions between lymphocytes and myeloid cells regulate pro- versus anti-tumor immunity - DeNardo, David G. (Springer US, 2010)
Tumor-associated myeloid cells have been implicated in regulating many of the “hallmarks of cancer” and thus fostering solid tumor development and metastasis. However, the same innate leukocytes also participate in anti-tumor immunity and restraint of malignant disease. While many factors regulate the propensity of myeloid cells to promote or repress cancerous growths, polarized adaptive immune responses by B and T lymphocytes have been identified as regulators of many aspects of myeloid cell biology by specifically regulating their functional capabilities. Here, we detail the diversity of heterogeneous B and T lymphocyte populations and their impacts on solid tumor development through their abilities to regulate myeloid cell function in solid tumors.